LES INVESTISSEMENTS DIRECTS ETRANGERS ET LA DIPLOMATIE DE NEGOCE AU RWANDA - Bofando, François Lisalu; Banza, Jean-Marc Banza wa (IJRDO - Journal of Social Science and Humanities Research, 2018)
Rwanda put in place of reform them in the key sectors of the economic life in order to attract the foreign direct investments. To arrive there, the Rwandan government granted a lot of easiness to the foreign investors. The Rwandan politics of struggle against the corruption improved the picture of the country in Africa and in the world. However, in spite of the foreign investments, the Rwandan population lives in misery. The country remains depending on the outside helps, the rate of unemployment increases. The strategy that consists in building the political stability of Rwanda on the destabilization of the neighbors to the ends to reach their resources illegally, doesn’t allow this country to use the diplomacy of commerce as instrument of rupture of the isolation and the emergence by interconnection.